THE EXPRESSION OF NATION-BUILDING AND THE CHARACTER-BUILDING SPIRIT AS FORMS OF NATIONAL IDENTITY AS OBSERVED IN THE ISTIQLAL MOSQUE’S ARCHITECTURE - Iqbal Ardiansyah; C. Sudianto Aly (Riset Arsitektur (RISA), 2017)
Abstract- A political regime generally possesses an identity and has insight into nationally idealistic cultural values. Its expression can be observed in the art and physical architecture that blossoms in its era. This insight gives birth to national identity. The formation of national identity itself originated from several dimensions, namely the sub-national dimension, the personal dimension, and the supra-national dimension. In the transition between the Netherland-East Indies and the Republic of Indonesia, Indonesia as a new country possessed ideals in the formation of physical architectures that can represent its national identity. This insight is realized in detail within nation-building and character-building ideas within several mega-projects pioneered by the Old-Order government. One of them was the Istiqlal Mosque as a national house of worship. The expression of Istiqlal Mosque architecture cannot be separated from the dimensions of national identity formation in architecture. The focus of this research is on the observation of Istiqlal Mosque architecture. Indicators of the national identity’s expression in Istiqlal Mosque architecture are: the discussion of national-identity dimensions in architecture (national-identity dimension – sub-national dimension, national-identity dimension – personal identity and national-identity dimension- supra-national identity). The discussions of expression in architecture that can be achieved through visual composition formation are (a) domination, (b) repetition, and (C) continuity in composition of one architectural object. The object of architecture was further examined, arranged by form and material, general design principles, contextual relations, and physical, semantic and spatial organization of an architectural object. The Istiqlal Mosque is one example of an architectural product from the previous political regime that can profoundly and critically sharpen our thoughts concerning the Indonesian nation’s identity on the national and state level. Keywords: national identity, nation-building and character-building, sub-national dimension, personal dimension, supra-national dimension, Istiqlal Mosque